The Analysis of Hierarchical Structure of Mesoporous Silica in Nanometer Scale by Small Angle Scattering Method - S. Hadi; S Suryajaya; I. Wijaya; A. Rahmandari; M.C. Prihatiningsih; I. Prasetyo; A. Patriati; E.G.R. Putra; S. Soontaranon (PPIKSN-BATAN, 2018)
The analysis of hierarchical structure of mesoporous silica material with template of cetyltrimethylammoniumbromide (CTAB) with co-surfactants of tetra-methylammonium hydroxide (TMAOH) and Triton X-100 was conducted by using the technique of small angle scattering (SAS) using neutron (SANS) and X-ray (SAXS). The analysis was supported by the data of nitrogen absorption and electron microscopy. The analysis showed that the concentration of CTAB affected the characteristics and pore structures of particles. The increase of co-surfactant concentrations tended to form particles that were more uniform in size and more regular in the shape of the sphere. The results of SAS analysis showed that the morphology, shape, and size of the large particles were arranged by smaller (primary or secondary) particles that had pores. The variation of surfactant templates had influenced the formation of pore structure. For CTAB-TMAOH, it would had resembled MCM-41 type which has a hexagonal structure, whereasfor CTAB-Triton X-100, it would have resembled MCM-48 type which has a cubic structure. The particles that have a high surface area which resembled pore structure MCM-41 has been able to set up by using 0.25 M of CTAB with 0.040 M of TMAOH. Moreover, the particles which resembled pore structure MCM-48 were able to set up by using 0.03 M of Triton X-100 with 0.4 M of CTAB. The analysis of SANS data that was supported by electron microscopy results is entirely showing a complete information of the particles formed by each template. Whereas SAXS analysis that supported by nitrogen adsorption method is fully confirming the information of pore characteristics.